Dual inhibition of AXL and MER kinase: scope for lung and breast cancer therapeutics - Sathe, Balaji Dashrath; Kumari, Pratibha; Kumar, Hemant; Mane, Madhav Shivaji; Mudududdla, Ramesh; Baell, Jonathan; Kumar, Roshan; Singh, Shareen; Pawar, D. K.; Kommi, Damodara N.; Bushi, Ganesh; Pathak, Prateek; et al. (Bioorganic Chemistry, 2025)
Cancer cells use multiple survival pathways for continuous proliferation, survival, and growth. Recent anticancer drug discovery commonly focuses on a single target that maintains key cancer cell survival mechanisms, where typically, this is a cellular enzyme that inhibits DNA replication, inducing cell damage and apoptosis. Since drugs that act on a single target may be more susceptible to the development of resistance, the search for polypharmacotherapeutics is becoming increasingly popular to defeat drug-resistant cancer cells. Receptor tyrosine kinases (RTKs) family members, AXL and MER, have been identified as important cancer targets and found to be overexpressed and associated with various forms of cancers, such as lung and breast cancers. This review has focused on the dual inhibition of AXL and MER kinases as a strategy for treating lung and breast cancer. The roles of these two kinases in non-small cell lung cancer (NSCLC) are such that dual inhibition would be therapeutically complementary, with MER inhibition more fully blocking tumor growth while AXL inhibition encourages chemosensitivity. Hence, treatment strategies targeting both of these RTKs may be more effective and beneficial than singly targeted agents, and a dual AXL/MER inhibitor is a potential therapy for NSCLC along with breast cancer. This review highlights the preclinical and clinical development of dual AXL and MER kinase inhibitors as lung and breast cancer treatments and the prospects for their future progression.
Keywords: AXL; Breast cancer; Cancer therapy; MER; Multi-kinase inhibitors; NSCLC targeted therapy